TGFβ1 induces Jagged1 expression in astrocytes via ALK5 and Smad3 and regulates the balance between oligodendrocyte progenitor proliferation and differentiation - Zhang, Yueting (2010)
Notch1 receptor signaling regulates oligodendrocyte progenitor differentiation and myelin formation in development, and during remyelination in the adult CNS. In active multiple sclerosis lesions, Notch1 localizes to oligodendrocyte lineage cells, and its ligand Jagged1 is expressed by reactive astrocytes. Here, we examined induction of Jagged1 in human astrocytes, and its impact on oligodendrocyte differentiation. In human astrocyte cultures, the cytokine TGFβ1 induced Jagged1 expression, and blockade of the TGFβ1 receptor kinase ALK5 abrogated Jagged1 induction. TGFβ2 and β3 had similar effects, but induction was not observed in response to the TGFβ family member activin A or other cytokines. Downstream, TGFβ1 activated Smad-dependent signaling, and Smad-independent pathways that included PI3 kinase, p38 and JNK MAP kinase, but only inhibition of the Smad-dependent pathway blocked Jagged1 expression. SiRNA inhibition of Smad3 downregulated induction of Jagged1, and this was potentiated by Smad2 siRNA. Purified oligodendrocyte progenitor cells (OPCs) nucleofected with Notch1 intracellular signaling domain displayed a shift towards proliferation at the expense of differentiation, demonstrating functional relevance of Notch1 signaling in OPCs. Furthermore, human OPCs plated onto Jagged1-expressing astrocytes exhibited restricted differentiation. Collectively, these data illustrate the mechanisms underlying Jagged1 induction in human astrocytes, and suggest that TGFβ1-induced activation of Jagged1-Notch1 signaling may impact the size and differentiation of the OPC pool in the human CNS.